Understanding the dynamics of compliance to smoke-free policy regulations: Exploring the perspectives of venue owners and staff in Türkiye - Baltaci, Ezgi; Çarkoğlu, Aslı; Saraf, Sejal; Ergüder, Toker; Ergör, Gül; Hayran, Mutlu; Hoe, Connie (Tobacco induced diseases, 2024)
INTRODUCTION: The study aims to understand the facilitators and barriers associated with enforcing and complying with Türkiye's smoke-free policy from the perspective of hospitality venue owners and employees. - METHODS: A qualitative open-ended survey was conducted in Istanbul and Ankara in 2021 with 58 respondents from 3 different districts in each city from four types of venues: restaurants, traditional coffee and waterpipe houses, and European-style cafés. The open-ended survey included questions to understand the knowledge, beliefs, and attitudes of respondents about Türkiye's smoke-free policy and their perceptions of the facilitators and/or barriers to smoke-free policy implementation and changes after COVID-19. The data were analyzed using an inductive approach to identify patterns and categorize the data into themes. - RESULTS: The respondents expressed that the smoke-free policy aimed to protect employees and customers from secondhand smoke (SHS), respect human health, and improve air quality. Findings suggest that the positive attitude of venue owners and staff toward the smoke-free policy serves as a facilitator. However, fear of financial impact, customers' negative attitudes, difficulties in meeting physical requirements, and insufficient enforcement were found to be barriers to implementing the smoke-free policy. The effects of the COVID-19 pandemic were reported as an initial increase in compliance and awareness among customers and staff, but some respondents noted negative changes due to the emotional and financial effects of prolonged restrictions. These challenges have led to decreased attention on the smoke-free policy among venue owners, staff and customers. Respondents' suggested improvements were related to building infrastructure, such as the ventilation systems and educating the public on the harmful health effects of smoking. - CONCLUSIONS: Despite the general understanding of the dangers of secondhand smoke and the smoke-free policy, this study highlights the challenges in implementing smoke-free policy measures and the continued need to raise awareness about the importance of a 100% smoke-free venue. A comprehensive approach to addressing the tobacco epidemic as a multifaceted public health issue is essential.
Gesehen am 06.08.2024